BLENDED LEARNING IN HERITAGE CONSERVATION COURSE: CULTURAL MAPPING AND GOOGLE MY-MAPS PLATFORM - Arif Budi Sholihah; Johannes Widodo (Dimensi: Journal of Architecture and Built Environment, 2018)
This paper attempts to evaluate the effectiveness of blended learning in Heritage Conservation course, at the Department of Architecture Universitas Islam Indonesia Yogyakarta using both a mini-workshop in a historic district (cultural mapping) and Google My-Maps Platform (digital collaborative) as learning tools to achieve the learning outcomes. The overall finding shows that cultural mapping, as the first-hand information gathering of a heritage district gives the student understanding which then allows the students not only to appreciate the importance of heritage but also having empathy that heritage is not only about artifacts or architecture (tangible assets) but more about people who live in it. Meanwhile, Google My-Maps Platform offers an opportunity for the students to work together in different places and gives the flexibility on the digital learning process both in the heritage district, in the class, and at home. The result from the cultural mapping arranged in the My-Maps in many different forms, such as story/narratives, photos, and videos before producing the report on revealing the “DNA” of the heritage district and can be shared for the benefit of the public. This research has shown that blended learning (online and offline learning) is more effective in architectural education for it is more flexible but still allow the students to get direct experience with the real world.